Correlating synthesis parameters with physicochemical properties of poly(glycerol sebacate). (February 2017) - Conejero-García, Álvaro; Gimeno, Héctor Rivero; Sáez, Yolanda Moreno; Vilariño-Feltrer, Guillermo; Ortuño-Lizarán, Isabel; Vallés-Lluch, Ana
Graphical abstract: Highlights: Crosslinking density of poly(glycerol sebacate) depends on curing conditions. Rinsing in an affine solvent is imperative to avoid diffusion of loose chains in use. Equimolar reagents ratio and curing at 130 °C/48 h lead to dense non-swellable meshes. Curing under milder conditions lead to poorly crosslinked hydrolysable networks. Abstract: Poly(glycerol sebacate), PGS, is an elastomeric biodegradable polyester increasingly proposed in a variety of biomedical applications. It is prepared by polycondensation of sebacic acid and glycerol in a first stage in which a prepolymer is obtained, followed by a curing to conveniently crosslink it. In this work, synthesis parameters such as the curing temperature and time, and the molar ratio between reactants, were systematically varied to correlate them with the physicochemical properties of the resulting polymer networks. The efficiency of each manufacturing process was quantified through the relative mass effectively crosslinked and insoluble in tetrahydrofuran. Infrared spectra gave an estimation of the ratio of non-condensed polar terminal groups. These results were correlated with swelling results, which in turn provided the means to calculate the chains density through Flory-Rehner equilibrium swelling equation for lightly crosslinked polymers. The role of the synthesis parameters on the physical state of the resulting polymers, as well as their proneness to hydrolyze, were followed. The results obtained highlight the relevance of rinsing them following synthesis, to remove non-crosslinked chains that easily diffuse to the surrounding medium. Curing under mild conditions equimolar mixtures of sebacic acid and glycerol proved to lead to poorly crosslinked swellable networks, which hydrolyze easily in bulk mode. Alternative molar ratios yield sticky and difficult to handle materials at higher polyol fractions in the reactive mixture, whilst an excess of acid terminal groups leads to a faster mass loss by hydrolysis in aqueous media together with surface salts deposition, concomitant with a lesser cell viability in in vitro culture. PGS synthesized from an equimolar ratio between reactants and cured at 130 °C or higher, for 48 h or longer, show suitable features for their use in tissue engineering applications where hydrophobic surface-degradable rubbers are required, without significant differences among them.